Critical Pedagogy through Genre-Based Pedagogy for Developing Students' Writing Skills: Strategies and Challenges - Qoyyimah, Uswatun; Agustiawan, Yosi; Phan, Thanh-Thao Thi; Maisarah, Maisarah; Fanani, Achmad (NOBEL: Journal of Literature and Language Teaching, 2022)
This current study discusses critical pedagogy, a concept that supports the paradigm of education for cultural transformation. This concept has been considered an essential approach for developing students' critical thinking and awareness of social issues. Despite its popularity, the implementation of critical pedagogy in classes remains unclear. This paper suggests that critical pedagogy can be concurrent with genre-based pedagogy (GBP), the dominant approach to teaching writing in Indonesia's English language classes. This study argues that language teachers can use GBP to introduce critical pedagogy. This research used descriptive qualitative method, allowing researchers to collect the data from classroom observation in vignettes. The data were taken from four classes where the participant teacher trained students to write argumentative texts. It captured the teaching and learning process in the Context Building and Text Modelling phases. The researchers interpreted and analyzed the data based on the themes identified from the critical pedagogy and GBP literature. It is found that the principles of critical pedagogy such as historicity, problem-posing, emancipation, and dialogic are evident in this study. This study has implications for EFL teachers in Indonesia, especially when they must adapt to "Merdeka Belajar," which promotes critical thinking.